Tradisi Kalindaqdaq Di Balanipa Kabupaten Polewali Mandar - Nurannisa Nurannisa; Hardiman Hardiman; Nisma Nisma (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study found that: first, the background of the emergence of Kalindaqdaq is pau-pau (talk) there is a mixture of Malay culture which then makes Kalindaqdaq have rhymes and is arranged like Malay pantun. Second, in the implementation of the Kalindaqdaq tradition, it is carried out by people who are holding a wedding or other events that are considered important. In terms of a wedding party, this event is usually carried out by the bride's party, before the marriage contract is held first, the khatam Qur'an at that time the person who is being khatam is paraded to his teacher's house or to the place where the Kuda Pattu'du (Dancing Horse) event is usually held. Third, the manifestation of Islamic values ​​in the Kalindaqdaq tradition is to arouse a sense of holiness for the local community, as well as being a guideline in determining their daily attitudes and behavior, improving the Islamic religious life of the Mandar community in realizing cultural resilience, peace and national unity. The four meanings of the symbols in the Kalindaqdaq tradition are the presence of a group of tambourines which are used as a symbol of fulfilling vows, the presence of Pakkalindaqdaq who is the person in charge of reading pantun in the Mandar language throughout the procession as a symbol of entertainment which is always greeted by the audience with responses, shouts, jokes or applause, and showing his ability to string together words and language containing religious messages and giving advice in front of the horses.